Mulberry fruit post-harvest management: Techniques, composition and influence on quality traits -A review. (October 2022) - Herman, R.A.; Ayepa, E.; Fometu, S.S.; Shittu, S.; Davids, J.S.; Wang, J.
Abstract: The mulberry ( Morus sp. ) fruit is noted for its yield during a fruiting season and a long history of usage as an edible fruit coupled with its medicinal qualities, particularly in Asia. However, its rapid postharvest decay has raised major concerns about the sustainability of the fruit both for food and economic purpose. For reasonably solid evaluations of postharvest preservations of produces, consideration must be committed to the viability of different control measures. In this review, we first highlight the nutritional composition of the fruit and some factors contributing to its rapid decay. Some alternative means of postharvest management including physical, chemical and biological procedures involved in preserving the fruit will be reviewed. Finally, the influence of management practices on the quality traits of the fruit will be summarized. The search for increasingly natural and sound sustenance products, based on insignificantly handled practices has brought about an expansion in customer necessities for safe and quality products, hence this review is focused on the preservation methods that are suitable to extend the shelf life of mulberry fruit.